(untitled) (Journal of Asian Development Studies, 2024)
This study is organized to determine the performance of economic growth in theFrench economy. For this purpose, this study considers the role of energy consumption, trade openness and consumer prices as determining factors. The ARDL bounds test will be used for the sample from 1986 to 2022 to obtain empirical results. The results confirm that economic growth and its determinants are cointegrated in the long run. Moreover, the results also reveal that only energy consumption and trade openness significantly boost economic growth. It is further witnessed that capital accumulation is expanding economic growth in France. Among these three factors, trade openness’s impact is stronger than the other factors taken in this research.